Nowcasting risk of poverty and income distribution in the EU in 2013 - Chrysa Leventi; Jekaterina Navicke; Olga Rastrigina; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2014)
The at-risk-of-poverty rate is one of the three indicators used for monitoring progress towards the Europe 2020 poverty and social exclusion reduction target. Timeliness of this indicator is critical for monitoring the effectiveness of policies. However, due in part to the complicated nature of the European Union Statistics on Income and Living Conditions (EU-SILC), estimates of the number of people at risk of poverty are published with a 2 to 3 year delay. This paper presents a method of estimating ('nowcasting') the current distribution of income between households, including the at-risk-of-poverty rate, using a tax-benefit microsimulation model (EUROMOD) based on the EU-SILC, combined with up-to-date macro-level statistics. The method is applied to 13 EU Member States experiencing differing economic conditions over the period, including those which have been affected comparatively little by the crisis as well as those which have suffered a major reduction in economic activity and employment.
Keywords: C81; H55; I3; 330; Nowcasting; European Union; Income distribution; Microsimulation